Duality Property of Discrete Quaternion Fourier Transform - Supriadi, Yudhiyanto; Bahri, Mawardi; Amir, Amir Kamal (Jurnal Matematika, Statistika dan Komputasi, 2020)
We introduce the discrete quaternionic Fourier transform (QDFT), which is generalization of discrete Fourier transform. We establish the version discrete of duality property duality related to the QDFT.